Program Pemberdayaan Masyarakat Difabel Melalui Difabel Creative Center di Daarut Tauhiid - Muhammad Rival Bisqi; A.Bachrun Rifa’i; Ali Azis (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
The aim of this research is to find out the process, implementation and results of community empowerment through the disabled creative center (DCC) program which is specifically for people with disabilities in the city of Bandung and is managed by DT – Peduli. The research method uses a descriptive method with a qualitative approach. The results showed that the DCC program took the form of sewing skills training, screen printing training, clothing production, and marketing of products. With the implementation, this meeting is carried out on a scheduled and neatly packaged basis which is inserted with a program of guidance on physical and spiritual motivation in the form of mini seminars, workshops or thematic training guided by successful experts and practitioners and Second, the Disability Workshop is a space to facilitate the potential possessed by the participants or DCC alumni so they can display their superior products or expertise profiles offline and online. As for the results of the DCC program, people with disabilities in the city of Bandung are able to improve their standard of living and are more empowered after participating in the disabled creative center (DCC) program.